Study of the Knowledge Contained in Software Components’ Identifiers - Anquetil, Nicolas (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2000: Anais do XIV Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2000.25922, 2000)
Maintaining old software, designed with obsolete methods, and poorly structured, is a knowledge intensive and difficult task. To help in this task, Reverse Engineering seeks to offer tools and analysis techniques that will help creating an abstract representation (a model) of a software system. We believe that one should take advantage of any available source of information to help in this task and know precisely what each source has to offer. In this paper we study the knowledge contained in the name of software components. Such study is needed to ascertain if this knowledge could be of use for Reverse Engineering, and to perform what activity? Our conclusions are that there is certainly interesting information to be extracted from identifiers, but that alone they may not be sufficient, and other sources, such as comments, would provide a welcome help.